University-Industry-Government Integration in the Development of Sustainable and Cost-Efficient Solutions for the Shrimp Sector in Colombia: Nutriaqua Case - Juan Sepúlveda; Alberto Albis; José Santamaría; Sigifredo Cervera (Journal of Sustainable Development of Energy, Water and Environment Systems)

(untitled)
This paper presents a case study, and lessons learned that illustrates the development of a cost-efficient and sustainable solution for shrimp farming sector in Colombia, using the model of Technology Readiness Level with stages from 1 to 9, and analizing the the participation and linkage of quadruple helix actors. The focus was on the development of this product considering that feeding and fattening represents approximately 40% of production costs. The solution was designed in a sustainable way, using local raw materials, resulting in a significant reduction in water and energy consumption during the process. This involved local communities and small producers, as well as shrimp and feed-producing companies, making possible to address multidimensional challenges and leverage diverse knowledge to optimize the solution. An iterative process of tests and improvements was carried out, validating its efficiency and feasibility in real conditions. The participation of the quadruple helix guaranteed a comprehensive vision and effective adaptation to meet the needs of producers. The result was the creation of a spin-off, a technology-based company which allows the effective transfer of technology and knowledge, facilitating the widespread adoption of the solution in the shrimp farming industry.